Merevitalisasi Spirit Pengabdian: Strategi Komunikasi Bela Negara bagi Aparatur Sipil Negara di Tengah Apatisme Birokrasi - Sukoco Henry Saputro; Aris Sarjito; Editha Praditya Duarte (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
National defense is a fundamental ethos for the State Civil Apparatus (ASN) in Indonesia, playing a crucial role in maintaining national stability through the provision of quality public services that have a positive impact on society. However, the implementation of the spirit of National Defense within bureaucracy is often hindered by deep-rooted apathy and cynicism, caused by various internal issues such as politicization, feudal culture, and low motivation among ASN. The gap between the idealism of public service dedication and the reality of bureaucratic pathology creates significant challenges in improving the quality of public services provided by ASN. This article aims to formulate a strategic communication framework that can revitalize the spirit of National Defense by addressing the root causes of apathy. The research uses a qualitative literature review methodology, analyzing indexed journals, regulations, and relevant institutional reports. The findings show that traditional communication approaches, which are dogmatic and one-way, are no longer effective in driving change within bureaucracy. Therefore, this article proposes a new communication paradigm that focuses on developing Public Service Motivation (PSM) as a solution to strengthen the spirit of National Defense. The recommended framework emphasizes the central role of transformational leadership and dialogical communication in translating the values of National Defense into meaningful and relevant goals for ASN's daily tasks. The strategy includes stages such as diagnosing existing problems, designing a participatory vision, mobilizing through change agents, empowering by removing systemic barriers, and reinforcing through recognition of performance based on integrity. Thus, communication of National Defense can transform from a ceremonial obligation into a source of pride and authentic professional work ethos. The implementation of this strategy is expected to increase ASN motivation to provide better public services that align with national values and create a more effective and competitive bureaucracy.